2022
DOI: 10.3389/fnut.2022.820224
|View full text |Cite
|
Sign up to set email alerts
|

Infant Formula Supplemented With Milk Fat Globule Membrane, Long-Chain Polyunsaturated Fatty Acids, and Synbiotics Is Associated With Neurocognitive Function and Brain Structure of Healthy Children Aged 6 Years: The COGNIS Study

Abstract: BackgroundAdequate nutrient intake during the first few months of life plays a critical role on brain structure and function development.ObjectivesTo analyze the long-term effects of an experimental infant formula (EF) on neurocognitive function and brain structure in healthy children aged 6 years compared to those fed with a standard infant formula or breastfed.MethodsThe current study involved 108 healthy children aged 6 years and participating in the COGNIS Study. At 0–2 months, infants were randomized to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 112 publications
(131 reference statements)
0
6
0
Order By: Relevance
“…However, thus far the results are inconsistent and sometimes controversial. Although the effect of PE on language abilities has not been specifically reported in the literature, the milk fat globule membrane (MFGM), which is a diverse mixture of bioactive components including phospholipids, has been shown to improve visual function, language, and motor domains in both term and preterm infants ( 16 , 54 , 55 ). In contrast, DHA has been reported to improve language ability.…”
Section: Discussionmentioning
confidence: 99%
“…However, thus far the results are inconsistent and sometimes controversial. Although the effect of PE on language abilities has not been specifically reported in the literature, the milk fat globule membrane (MFGM), which is a diverse mixture of bioactive components including phospholipids, has been shown to improve visual function, language, and motor domains in both term and preterm infants ( 16 , 54 , 55 ). In contrast, DHA has been reported to improve language ability.…”
Section: Discussionmentioning
confidence: 99%
“…MFGM components positively influence brain development ( 60 ). Recent results from the COGNIS study suggest that the supplementation of infant formulas with MFGM components, LC-PUFAs, and synbiotics could be associated with beneficial long-term effects on neurocognitive development and brain structure at 6 years old ( 61 ). Gangliosides have important functions in neurogenesis and neural repair, being in great abundance during development in the hippocampal region of the brain, which is responsible for memory and higher cognitive function ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…During SIF digestion, the fatty acid contents in eHIF were also higher than that in sIF and pHIF, especially LCPUFAs (Figures 3C,F,I). Numerous studies have shown that LCPUFAs containing n-3 and n-6 fatty acids (e.g., α-linoleic acid C18:3, n-3; linoleic acid C18:2, n-6) contribute to the infant nervous system and retina development (38,39), suggesting that eHIF had a better nutrient composition and promoted brain development after digestion. However, the contents of most fatty acids were not significantly different between sIF and pHIF samples.…”
Section: Characteristics Of Fatty Acids In Infant Formula During In V...mentioning
confidence: 99%
“…For the pHIF group, the number of arm entries and turns were significantly lower than those of the other three groups (p < 0.05). A possible reason for this result was that the abundant fatty acid content in eHIF, especially LCPUFAs (Figure 3), promoted the development of mouse brain (39), thereby improving maze test performance. Fewer LCPUFAs in pHIF (Figure 3) might be responsible for the lower total number of arm entries and turns observed for this group of mice.…”
Section: Hydrolyzed Infant Formula Could Affect Intelligence and Phys...mentioning
confidence: 99%